Progress in Pretreatment and Analysis of Cephalosporins: An Update Since 2005. (12th March 2021) - Duan, Xiao-Yi; Zhang, Yuan; Yan, Jia-Qing; Zhou, Yu; Li, Guo-Hui; Feng, Xue-Song
Abstract: Cephalosporins, one of the classic β-lactam antibiotics, has been widely concerned by global population as the most commonly used broad-spectrum antibiotic. Serious health hazards are possible to be posed by quality control problems caused by its unstable structure, as well as food and environmental pollution introduced by improper use. Given the reasons above, the sensitive and valid methods for monitor and determination of cephalosporins in different matrices are urgently required. This review aims to provide a comprehensive overview on the current status of the pretreatment and analysis methods of cephalosporins in bulk drug, pharmaceutics, animal-derived foodstuffs including eggs, milk, meat, environment samples, and biological samples. Pretreatment methods including simple steps (protein precipitation, centrifugation, filtration), liquid-liquid extraction, solid phase extraction, QuECHERS, and detection methods covering LC, LC-MS/MS, voltammetric sensor, capillary electrophoresis spectroscopy, biological methods from January 2005 to October 2018 are updated, elaborated and compared here. Moreover, advanced materials and prospects for development are discussed. Highlights: Determination of cephalosporins in different newly found matrix are represented. Comparisons between different mass analyzers and progress in HRMS methods are in detailed. Optimization of experimental conditions are discussed. Newly emerged eco-friendly methods are introduced. Graphic Abstract: